Effectiveness of Midwife Emotional Support on Anxiety Levels of Pregnant Women: a Systematic Literature Study - Olyvia Rosalia; Firayani; Komala Dewi Muslimin (PT. Anagata Sembagi Education, 2025)
Pregnancy is a period full of physical and emotional changes that can trigger anxiety in pregnant women. Emotional support from midwives, as frontline healthcare providers, plays a crucial role in reducing this anxiety. This study aims to systematically review the effectiveness of emotional support provided by midwives on the anxiety levels of pregnant women. The method used involved a literature search from databases such as PubMed, Scopus, and Google Scholar using the keywords “midwife emotional support,” “pregnancy anxiety,” and “maternal mental health.” The results from 10 reviewed studies indicate that emotional support from midwives through counseling, empathetic communication, and home visits—significantly reduces anxiety levels in pregnant women. This study recommends enhancing empathetic communication training for midwives in antenatal care services.